Understanding the Mechanisms of Proteinuria: Therapeutic Implications - Toblli, Jorge Eduardo (2012)
A large body of evidence indicates that proteinuria is a strong predictor of morbidity, a cause of inflammation, oxidative stress and progression of chronic kidney disease, and development of cardiovascular disease. The processes that lead to proteinuria are complex and involve factors such as glomerular hemodynamic, tubular absorption, and diffusion gradients. Alterations in various different molecular pathways and interactions may lead to the identical clinical end points of proteinuria and chronic kidney disease.ffusion gradients. Alterations in various different molecular pathways and interactions may lead to the identical clinical end points of proteinuria and chronic kidney disease.fferent molecular pathways and interactions may lead to the identical clinical end points of proteinuria and chronic kidney disease.